2012
DOI: 10.1016/j.reprotox.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electronic cigarette refill fluid cytotoxicity using embryonic and adult models

Abstract: a b s t r a c tElectronic cigarettes (EC) and refill fluids are distributed with little information on their pre-and postnatal health effects. This study compares the cytotoxicity of EC refill fluids using embryonic and adult cells and examines the chemical characteristics of refill fluids using HPLC. Refill solutions were tested on human embryonic stem cells (hESC), mouse neural stem cells (mNSC), and human pulmonary fibroblasts (hPF) using the MTT assay, and NOAELs and IC 50 s were determined from dose-respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
373
4
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(405 citation statements)
references
References 23 publications
22
373
4
6
Order By: Relevance
“…Whilst E‐cigarettes are a relatively new product on the market, many papers now show that they too have toxic effects on a range of cells (Bahl et al. 2012; McGrath‐Morrow et al. 2015; El Golli et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst E‐cigarettes are a relatively new product on the market, many papers now show that they too have toxic effects on a range of cells (Bahl et al. 2012; McGrath‐Morrow et al. 2015; El Golli et al.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is non‐nicotine dependent, and there has been particular interest in certain flavors including tobacco, cherry, and cinnamon, that have been shown to be more toxic than others (Bahl et al. 2012; Behar et al. 2014; Kosmider et al.…”
Section: Discussionmentioning
confidence: 99%
“…ENDS solutions have also been shown to be cytotoxic to human embryonic stem cells. 40 These studies raise concern for harm from in utero exposure and neonatal exposure to nicotinecontaining ENDS solution.…”
Section: Ends Secondhand and Thirdhand Aerosolmentioning
confidence: 99%
“…In fact, the Flavors and Extracts Manufacturers' Association (FEMA) has issued an official statement mentioning that flavor ingredients are evaluated for exposure through ingestion only; thus, any results cannot be extrapolated to use through inhalation. 5 Studies have shown that any cytotoxic properties of e-cigarette liquids and aerosol, although significantly lower than tobacco smoke, may be attributed to specific flavors, [6][7][8] indicating that further research is certainly needed in this area.…”
Section: Introductionmentioning
confidence: 99%